Product Fit and Sizing : Sustainable Product Evaluation, Engineering, and Design - Kathleen M. Robinette; Daisy Veitch; Sandra Alemany; Karen Bredenkamp (CRC Press, 2024)
In this book, for the first time, the complexity of assessing fit and using fittings in the product design process is addressed from a scientific and systems engineering perspective. It includes methods to represent the anthropometry of the target market, good practices to develop protocols for more reliable and consistent fit testing, methods for developing and maintaining a fit database, comprehensive statistical analyses needed for fit and sizing analysis, and instructions for selecting and modeling cases for new product development.Product Fit and Sizing: Sustainable Product Evaluation, Engineering, and Design offers step-by-step instructions for the evaluation, engineering, and design of existing and new products and includes real-world examples of mass-produced apparel, head wearables, and footwear products. It also explains how to develop a sustainable fit standard for fit and sizing continuity for all styles across all seasons and iterations.This book is intended for industry professionals and undergraduate and graduate education to prepare students for design and engineering jobs. For organizations that purchase uniforms or protective equipment and apparel, it also provides instructions for purchasing professionals to evaluate the suitability of wearable products for their population.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.